Inter-organizational purchasing contracts: the effects of multi-agents in a supplying firm. Issue 1 (3rd January 2022) - Oh, Jae-Young; Choi, Ji-Hung (Ryan)
Abstract: We investigate how supplier performance is influenced by the behaviors (self-interested behaviors and gatekeeping actions) of a supplier's salesperson and engineer, and how such behaviors affect a performance-based contract design to ensure the desired performance from the supplier. This article develops a incentive contract that proves how such behaviors affect supplier performance, elucidating how agents' behaviors influence a buyer's incentive contract form for collaboration with the supplier. Our study found that in general, the behaviors of salespeople and engineers can damage supplier performance. Their impact changes depending on some contingent factors, proposing incentive contract forms that can mitigate the negative consequences of the behaviors on supplier and buyer performance. This paper takes multiple agents' behaviors and their behavioral disutility into consideration when developing an incentive contract.